2003
DOI: 10.1080/11250000309356500
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation and phylogeography of roe deer in Spain, as suggested by mitochondrial DNA and microsatellite analysis

Abstract: Current population structure patterns of roe deer Capreolus capreolus in Spain were assessed through the analysis of mitochondrial and nuclear DNA. Restriction fragment length polymorphism was detected in the D-loop and NADH-dehydrogenase ND1 segments of mitochondrial DNA. Nuclear variation was investigated using 12 microsatellite loci. A total of 126 roe deer were analysed from fourteen sampling sites across the Iberian peninsula, including the Andalusian population from Sierra de Cádiz, which represents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 41 publications
3
22
0
10
Order By: Relevance
“…Although the Italian and European forms show overall similar autoecology and behaviour (social aggregation and large familiar areas during winter; dispersal and small familiar areas in summer), it has been suggested that the Italian roe deer may prefer wooded and scrubland areas, where higher-quality food may be found, especially in summer (Focardi et al 2008). Recently, levels and patterns of mtDNA polymorphism have been analyzed in several populations of European and Siberian roe deer (Randi et al 1998;Wiehler & Tiedermann 1998;Lorenzini et al 2003;Royo et al 2007), with special attention to natural and reintroduced individuals from the Alps and central Italy (Lorenzini et al 2002;Vernesi et al 2002;Randi et al 2004;Lorenzini & Lovari 2006). Although those studies did not entirely agree in identifying the postglacial re-colonization routes to northern Europe, they all revealed high levels of genetic structuring among roe deer populations across Europe and in particular between populations from the southern regions.…”
mentioning
confidence: 99%
“…Although the Italian and European forms show overall similar autoecology and behaviour (social aggregation and large familiar areas during winter; dispersal and small familiar areas in summer), it has been suggested that the Italian roe deer may prefer wooded and scrubland areas, where higher-quality food may be found, especially in summer (Focardi et al 2008). Recently, levels and patterns of mtDNA polymorphism have been analyzed in several populations of European and Siberian roe deer (Randi et al 1998;Wiehler & Tiedermann 1998;Lorenzini et al 2003;Royo et al 2007), with special attention to natural and reintroduced individuals from the Alps and central Italy (Lorenzini et al 2002;Vernesi et al 2002;Randi et al 2004;Lorenzini & Lovari 2006). Although those studies did not entirely agree in identifying the postglacial re-colonization routes to northern Europe, they all revealed high levels of genetic structuring among roe deer populations across Europe and in particular between populations from the southern regions.…”
mentioning
confidence: 99%
“…In this area, the species has evolved in very particular ecological conditions with a low density of individuals in a Mediterranean xerophytic forest. The identity of the C. c. garganta subspecies is doubtful (Aragó n et al, 1995b), although Lorenzini et al (2003) suggested a genetic differentiation between Andalusian and Northern roe deer in Spain. However, based on a limited sampling in the putative area of distribution of C. c. garganta, Randi et al (2004) suggest that the subspecies may have admixed origins and that its monophyly would be not supported by molecular data.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, mainly using mitochondrial (mt)DNA information (Wiehler and Tiedemann, 1998;Randi et al, 1998Randi et al, , 2004Vernesi et al, 2002;Lorenzini et al, 2003), have shown that the roe deer population in Europe has a significant structuring consistent with the cycles of restriction and colonization induced by the last glacial oscillations. As seen for a wide variety of European flora and fauna (see Taberlet et al, 1998 andHewitt, 1999 for reviews), these studies have consistently identified three regions: the Iberian Peninsula, Italy and the Balkans, as glacial refugia for the species.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation of the European roe deer divides into central, eastern and western lineages. The central lineage is widespread throughout Europe, whereas the eastern lineage is found mainly in Greece and Serbia and the western lineage is mainly in Spain and Portugal (see Lorenzini et al, 2003;Randi et al, 2004;Lorenzini and Lovari, 2006). In addition to these divisions, significant internal structuring has been detected in roe sampled from the Italian and Iberian peninsulas.…”
Section: Introductionmentioning
confidence: 96%